METODE PEMBELAJARAN BAHASA ARAB DI MADRASAH TSANAWIYAH MATHAL’UL ANWAR SIDOWALUYO KALIANDA KABUPATEN LAMPUNT SELATAN: METODE PEMBELAJARAN BAHASA ARAB - Andi Saputra; Khairil Anwar (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2018)
Madrasah Tsanawiyah Mathla'ul Anwar Sidowaluyo Kalianda is one of the formal institutions that provides Arabic learning facilities for their students. The Arabic learning method in MTs MA Sidowaluyo Kalianda will be examined there. The results showed that there was an increase in the average value of students and the percentage of students who got grades from 6 up with prior to conducting research, which are from the three cycles more than 50% of students got grades from 6 upwards and the average student in all three cycles, they are: cycle 1 is 6.6, cycle 2 is 6.6, and cycle 3 is 6.2, whereas before research is conducted the average student score is 4.8 and students who get grades from 6 upwards are less than 50 %.